1996
DOI: 10.1542/peds.98.4.730
|View full text |Cite
|
Sign up to set email alerts
|

Iodine, Thyroid Function, and Very Low Birth Weight Infants

Abstract: Objective. Research was undertaken to test two hypotheses. First, during the early neonatal period, thyroid function of very low birth weight (VLBW) infants is suppressed by exposure to iodine-containing antiseptic solutions and/or iodized contrast media. Second, this suppression is more pronounced in small for gestational age (SGA) infants. Methods. Urinary iodine concentration and thyroid function measurements were obtained prospectively from 44 VLBW infants with gestational ages at birth of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…14 Additionally, excessive consumption of certain iodized products can result in hyperthyroidism and hypothyroidism, thus impacting neonatal growth and development. 15 Epidemiological data reveal a strong correlation between phthalate exposure and maternal thyroid hormone levels. 16−19 Furthermore, neonatal umbilical cord blood serum thyroid stimulating hormone (TSH) and tetraiodothyronine (TT4) levels have shown negative correlation with umbilical cord serum monobutyl phthalate (MBP) levels.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Additionally, excessive consumption of certain iodized products can result in hyperthyroidism and hypothyroidism, thus impacting neonatal growth and development. 15 Epidemiological data reveal a strong correlation between phthalate exposure and maternal thyroid hormone levels. 16−19 Furthermore, neonatal umbilical cord blood serum thyroid stimulating hormone (TSH) and tetraiodothyronine (TT4) levels have shown negative correlation with umbilical cord serum monobutyl phthalate (MBP) levels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…High levels of thyroxine caused by hyperthyroidism raise the probability of low birth weight in comparison to maternal health. Furthermore, a methodical review indicated that numerous clinical indications in preterm/low-birth-weight babies are caused by hypothyroidism . Additionally, excessive consumption of certain iodized products can result in hyperthyroidism and hypothyroidism, thus impacting neonatal growth and development . Epidemiological data reveal a strong correlation between phthalate exposure and maternal thyroid hormone levels. Furthermore, neonatal umbilical cord blood serum thyroid stimulating hormone (TSH) and tetraiodothyronine (TT4) levels have shown negative correlation with umbilical cord serum monobutyl phthalate (MBP) levels .…”
Section: Introductionmentioning
confidence: 99%